Making Bah Biak Waterfall Tourism Promotion Video in Desa Bah Biak Kecamatan Sidamanik Kabupaten Simalungun - Bukit, Ferry Rahmat Astianta; Safril, Muhammad; Nasution, Zaid P (Talenta Publisher, 2022)
The Covid-19 pandemic is believed to be a turning point for changes in tourism and the design of creative economy business models, including in Indonesia. Through the Ministry of Tourism and Creative Economy, the government prepares various policy directions and strategies in tourism promotion programs during the pandemic and post-pandemic in Indonesia. Sidamanik District is one of the sub-districts in the Simalungun Regency, North Sumatra Province, which has considerable natural potential, namely natural potential in the form of landscapes such as the Bah Butong Sidamanik tea garden, Bah Manik baths, and Bah Biak Waterfall. Bah Biak Waterfall has its uniqueness. Bah Biak Waterfall has a height of approximately 20 meters which immediately falls into the rocks and a swimming pool provided by the manager. The current condition experienced is the lack of visitors who come to tourist objects due to the lack of marketing and information disseminated to the broader community, especially during a pandemic like today. Along with technological advances, the development of promotional media began to shift to digital media, one of which was video. Therefore, through community service, which is one of the tri dharma of higher education and to support Strategy 7 of the Ministry of Tourism and Creative Economy: Utilization of technology to support tourism marketing and the creative economy, our service team proposes making tourism promotion videos through video/ Digital Marketing of Bah Biak Tourism Object in Bah Biak Village, Sidamanik District. Through this video, we hope to positively impact tourist destinations, including a significant increase in the tourism sector.